Implementasi Nilai-Nilai Pancasila Di Sekolah Muhammadiyah - Mahfudloh, Azhari; Marzuki, Ismail; Masub Bakhtiar, Afakhrul (Prodi Pendidikan Guru Sekolah Dasar, 2024)
This research aims to describe the implementation of Pancasila values in Muhammadiyah schools, supporting factors, inhibiting factors and school efforts in implementing Pancasila values. Muhammadiyah schools are Islamic educational institutions that are closely related to the practice of Pancasila values, the main teachings of which are Al-Qur’an and As Sunnah. This research took place at MI Muhammadiyah 1 Pantenan, motivated by an effort to strengthen Pancasila values in daily life based on awareness, not coercion. This research is descriptive qualitative research. The subjects are school principals, teachers and students. The data collection techniques used were observation and interview techniques. The instruments in this research include observation sheets and interview guides. The data analysis techniques used by researchers are through the process of data reduction, data presentation and drawing conclusions. The validity of the data is obtained through the stages of source triangulation and technical triangulation. The research results show that; (1) MI Muhammadiyah 1 Pantenan School has implemented Pancasila values which contain divine values, human values, unity and oneness values, deliberation values, and social justice values in the school environment and learning activities (2) supporting factors namely the school principal, teachers , parents or guardians of students, school environment, facilities and infrastructure (3) inhibiting factors come from the external environment, finances, and parents of students who do not support school activities and students who are difficult to control (4) school efforts, namely running school programs optimally , habituation at school, adding coaching hours and always providing motivation for students.